Effects of Hypoxic Stress on Electrolyte Levels of Blood in Juvenile Rainbow Trout (Oncorhynchus mykiss) - Kelestemur, G. T. (Iranian Fisheries Science Research Inst-Ifsri, 2012)
[Abstract Not Available]
Keywords: Rainbow trout; Flow rate; Hypoxic stress; Blood electrolyte